Management of Learning Evaluation in Elementary Schools - Hisbullah Hisbullah; Andi Muhammad Ajigoena (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This article discusses the importance of learning evaluation in elementary schools and various approaches and strategies that can be used in managing evaluation. The article was born from a literature research type, which designs and collects data based on reading sources, both offline and online. The article explains that learning evaluation is an important process in assessing learning objectives and providing feedback to teachers and students to improve the quality of learning in elementary schools. The article also highlights several evaluation approaches such as formative and summative evaluation, as well as evaluation strategies such as the use of tests, observations, and portfolios. Additionally, the article emphasizes the important role of effective evaluation management in ensuring accurate and reliable learning evaluation. In conclusion, this article provides a broad overview of learning evaluation management in elementary schools and provides advice for teachers and principals to optimize the learning evaluation process in elementary schools.